Long-term agroforestry enhances soil organic carbon pools and deep soil carbon sequestration in the Indian Himalayas - Barman, Swarnashree; Bhattacharyya, Ranjan; Singh, Charan; Rathore, A. C.; Singhal, Vibha; Biswas, D. R.; Ahmed, Nayan; Das, Shrila; Kumar, Sandeep; Jat, S. L.; Das, T. K.; Kumar, Soora Naresh; et al. (Frontiers in Environmental Science, 2025)
Despite agroforestry has large potential for soil organic carbon (SOC) sequestration, limited information is available on SOC pools and deep SOC sequestration as affected by agroforestry systems. Potential of long-term (15 years) agroforestry systems to store SOC was assessed in the foot hills of the north western Indian Himalayas. The study was carried out during 2009–2023 and soil samples were taken from four depths, viz. 0–15, 15–30, 30–45, 45–60 cm in Bhimal (Grewia optiva L.) and Mulberry (Morus alba L.) based agroforestry system under cowpea-toria based cropping systems and turmeric as ground storey crop. Results showed that in surface soil (0–15 cm), plots with mulberry + cowpea (Vigna unguiculata L.)-toria (Brassica campestris L.) (T7) had maximum C stock (21.35 Mg C ha−1) which was similar to mulberry + turmeric (Curcuma longa L.) (T6) plots. In deep soil layer (30–60 cm), plots under T7 had 33.52 Mg C ha-1 which was significantly higher than farmers’ practice cowpea-toria (T4). The results revealed that M. alba L. based agroforestry practices had 33%, 18% and 8% higher labile C concentration than (cultivated fallow land) (T9), T5 and T4 plots, respectively, in 0–15 cm soil depth. Recalcitrant C was maximum in T7 (4.49 g kg−1) plots. In the 0–30 cm layer, C accumulation rate ranged from 0.27 Mg C ha−1yr−1 to 0.99 Mg C ha−1y−1. Maximum C accumulation was found in T7 plots which was 160% and 135% higher than the farmers’ practise T4 plots and sole mulberry plantation (T5) plots. In the surface soil (0–15 cm), the treatment T7 had approximately 33% higher carbon management index (CMI) value compared with the farmers’ practise T4 plots. Thus, adopting M. alba L. based agroforestry practices has great potential for improving higher carbon stock in deep soil layer and can be recommended for sustainable management practices in the region, and it also could be considered as a strategy to restore degraded land, which is vital for food security, livelihood enhancement, and overall preserving the environmental services.